Модификация атразином и симазином ион-селективных свойств плазмалеммы клеток Nitella flexilis - Яковец, Оксана Геннадьевна; Юрин, Владимир Михайлович; Кудряшов, Анатолий Петрович; Лис, Елена Марьяновна (Минск : БГУ, 2003)
Using electrophysiological approaches to research of ion-selective properties of plasmalemma, change of coefficient Na7K+-selectivity (a) of plasmalemma of Nitella flexilis cells at presence s-triazine herbicides atrazine and simazine is established. It was shown that the increase a at presence 2,3-10_s M and 9,3-10-5 M atrazine is caused in the greater degree by reduction of permeability of plasmalemma to ions K4 (Pk) and at presence 9,9-10-3 M simazine increase of permeability of plasmalemma to ions of Na4 (F3Na)- The decrease of a at presence 4,6-10-5 M atrazine and 2,MO"5 M simazine is connected with the reduction of PNa. The cause of observable effects may consist in influence of s-triazines on K4-Channels of plasmalemma, and/or on a condition of lipid bilayer and a s-tria-plasmalemma to ions K4 (Pk) and at presence 9,9-10-3 M simazine increase of permeability of plasmalemma to ions of Na4 (F3Na)- The decrease of a at presence 4,6-10-5 M atrazine and 2,1-10-5 M simazine is connected with the reduction of PNa. The cause of observable effects may consist in influence of s-triazines on K4-Channels of plasmalemma, and/or on a condition of lipid bilayer and a s-triazine-ring of herbicides. Character of the changes of ion-permeability of a membrane is determined by a nature of alkylamine substituents in a s-triazine-ring of herbicides.